The first case of papillary thyroid carcinoma in an adolescent with congenital dyshormonogenetic hypothyroidism in Serbia - Eremija, Jelena; Milenković, Tatjana; Mitrović, Katarina; Todorović, Sladjana; Vuković, Rade; Plavšić, Ljiljana (Vojnosanitetski pregled, 2014)
Introduction. Differentiated thyroid carcinoma (DTC) is a rare childhood malignancy, as it represents 0.3–0.4% of pediatric malignancies. Papillary carcinoma is the most common type of pediatric DTC and it represents about 90% of all DTC patients. Although rare, DTC arising from dyshormonogenetic goiter is the most serious complication of congenital hypothyroidism. Case report. We presented the development of thyroid papillary carcinoma in a 15-year-old girl diagnosed with congenital dyshormonogenetic hypothyroidism at neonatal age. Considering the early initiation and proper dosage of hormonal substitution, normal levels of thyreotropin and thyroid hormones were achieved quickly and maintained through a follow-up period. The girl remained euthyroid and asymptomatic until 13.8 years of age, when she presented with a large multinodular goiter. The patient underwent total thyroidectomy. Pathological examination revealed intrathyroid microcarcinoma in the right lobe. Conclusion. Although differentiated thyroid carcinoma is a rare pediatric malignancy, it is of great importance to have a certain degree of clinical caution and provide a multidisciplinary approach during the follow-up of patients with dyshormonogenetic hypothyroidism.
Keywords: congenital hypothyroidism; thyroid neoplasms; carcinoma; papillary; thiroidectomy; child; treatment outcome; serbia